Analisis Estimasi Permintaan dan Penawaran Kredit Konsumsi di Sumatera Utara (Periode 1990-2011) - Martin Hansen Simaremare; Paidi Hidayat (Departemen Ekonomi Pembangunan USU, 2013)
This study aims to determine how much influence the Interest Rate and Per Capita Income of the consumer credit demand in North Sumatera as well as to determine how much influence the, Gross Domestic Regional Product and Non Performing Loan (NPL) to offer consumer credit in North Sumatera.In this study, data obtained from Bank Indonesia branch of North Sumatera, Central Bureau of Statistics of North Sumatera and other sources that is research result and journals. Data beginning in 1990-2011using Two Stage Least Square method.The results showed demand for consumer credit in North Sumatera, according to the results of TSLS influenced by Third Party Funds, Interest Rate and Income Per Capita. While consumer credit offering in North Sumatera by TSLS results are influenced by Third Party Funds.Keywords : Third Party Funds, Interest Rate, Per Capita Income, Gross Domestic Regional Product and Non Performing Loans(NPL)